2020
DOI: 10.3390/antibiotics9010029
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antibacterial Activity of Essential Oils from the Algerian Endemic Origanum glandulosum Desf. against Multidrug-Resistant Uropathogenic E. coli Isolates

Abstract: Antibiotics are becoming ineffective against resistant bacteria. The use of essential oils (EOs) may constitute an alternative solution to fight against multidrug-resistant bacteria. This study aims to determine the chemical composition of EOs from five populations of the endemic Algerian Origanum glandulosum Desf. and to investigate their potential antibacterial activity against multidrug-resistant uropathogenic E. coli strains. The EOs were obtained by hydrodistillation and their composition was investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Our results are in agreement with previous studies which documented the effectiveness of thymol and carvacrol compounds against various bacteria [ 46 ]. In addition, thymol and carvacrol were suggested as the bioactive compounds against Escherichia coli , Staphylococcus aureus, and Candida albicans [ 17 ].…”
Section: Resultssupporting
confidence: 93%
“…Our results are in agreement with previous studies which documented the effectiveness of thymol and carvacrol compounds against various bacteria [ 46 ]. In addition, thymol and carvacrol were suggested as the bioactive compounds against Escherichia coli , Staphylococcus aureus, and Candida albicans [ 17 ].…”
Section: Resultssupporting
confidence: 93%
“…During the vegetative stage, carvacrol and γ-terpinene achieved the highest amount while p-cymene reached its highest level at the fruiting stage. As thymol and carvacrol are important bioactive compounds supporting applications in pharmaceutical and food industries [37][38][39][40][41], the flowering stage of S. macrantha can be the best one to obtain a high quality EO. Previous studies indicated that thymol and carvacrol can be found in high amounts at the flowering stage in other Lamiaceae and Apiaceae species [37,42,43].…”
Section: Essential Oil Analysismentioning
confidence: 99%
“…Thymol and carvacrol are the most important components of O. decumbens EO; they are commonly found in several members of the Lamiaceae, Ranunculaceae, Apiaceae and Verbenaceae families. Numerous biological activities of these phenolic monoterpenes such as antioxidant, antiseptic, antibacterial, antifungal, antiviral, insecticidal, acaricidal, antiprotozoal, antispasmodic, growth promoter, anti-inflammatory and antitussive have been documented [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. These numerous properties of its main volatile compounds make this plant a valuable herb for cosmetic, food and feed, and pharmaceutical industries.…”
Section: Introductionmentioning
confidence: 99%